2009
DOI: 10.2334/josnusd.51.69
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a test dentifrice containing nano-sized calcium carbonate on remineralization of enamel lesions in vitro

Abstract: The efficacy of a test dentifrice containing nano-sized (several tens to hundreds of nm) calcium carbonate (hereafter NC) on enamel lesion remineralization was studied in an in vitro system that employed collagen-coated wells for cell culture, as a model of oral surfaces for NC retention. The well surfaces were treated with the test dentifrice and briefly rinsed with distilled water. Thin sections of enamel with artificial subsurface demineralization were remineralized in the plate wells containing remineraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 18 publications
0
39
0
2
Order By: Relevance
“…According to some studies, artificial saliva can mimic oral saliva in vitro and plays a role in remineralization. 16 Considering the results of the present study, if teeth have the opportunity to be in contact with artificial saliva after bleaching and before toothbrushing, surface roughness will be comparable to that of the control group. It is likely that precipitation of minerals present in the artificial saliva on tooth surfaces can play a role in decreasing the surface roughness of bleached enamel 18 ; however, further studies are necessary to evaluate the effects of different storage environments, such as artificial saliva and plain water, on changes in surface roughness of bleached enamel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some studies, artificial saliva can mimic oral saliva in vitro and plays a role in remineralization. 16 Considering the results of the present study, if teeth have the opportunity to be in contact with artificial saliva after bleaching and before toothbrushing, surface roughness will be comparable to that of the control group. It is likely that precipitation of minerals present in the artificial saliva on tooth surfaces can play a role in decreasing the surface roughness of bleached enamel 18 ; however, further studies are necessary to evaluate the effects of different storage environments, such as artificial saliva and plain water, on changes in surface roughness of bleached enamel.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the artificial saliva was as follows: 1.0 mM CaCl 2 , 3.0 mM KH 2 PO 4 , and 100 mM NaCl; the pH value was 6.30 and was adjusted with NaOH solution. 16 After the daily bleaching procedure, the specimens were rinsed with deionized distilled water for five seconds. Then the subsequent steps for each group were carried out as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, its applications as bone implant are being extensively investigated in a different variety of forms (Vandiver et al, 2005). Study conducted by Nakashima et al (2009) showed that there is 48.8% improvement on the remineralization of artificially produced subsurface enamel lesions when the nanosized calcium carbonate particles were incorporated in dentifrices. Furthermore, nanocarbonate apatite has proven to be very efficacious desensitizing dentifrice when compared with the conventional agents (Lee et al, 2008).…”
Section: In Preventionmentioning
confidence: 99%
“…Studies showed that nanoparticles of silver imparted high antibacterial activity on dental resins, which significantly reduces building-up of biofilm as well as lactic acid production by the oral bacteria without interfering with the resins' mechanical and physical properties (Cheng et al, 2015). In one investigation, carbonate hydroxyl apatite nanoparticles have been found to be highly effective in repairing some tooth defects (micrometer-sized) in vitro (Cheng et al, 2015), and some of its nanocrystals were incorporated in dentifrices like mouthwash solutions and toothpaste and used as commercial products (Lei et al, 2016;Nakashima et al, 2009).…”
Section: In Preventionmentioning
confidence: 99%
“…However, the 5-10 day in vitro study had neglected the conditions of the oral cavity. In another in vitro study, nano-sized amorphous calcium carbonate particles that were applied twice a day for a period of 20 days promoted remineralization of artificial white-spot enamel lesions (Nakashima et al, 2009). Reconstitution and remineralization of dentin using nano-sized bioactive glass particles and beta-tricalcium phosphate was also tested in vitro, however, the mechanical properties of original dentin could not be reproduced (Shibata et al, 2008;Vollenweider et al, 2007).…”
Section: Preventive Dentistrymentioning
confidence: 99%